2022
DOI: 10.3390/futurepharmacol2040037
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Its Compounds in the Treatment of Anxiety and Related Disorders: A Scoping Review of Translational and Clinical Research

Abstract: Anxiety disorders are among the most common mental disorders worldwide and often respond incompletely to existing treatments. Selenium, a micronutrient that is a component of several biologically active selenoproteins, is also involved in several aspects of brain functioning and may exert antidepressant and anxiolytic effects through multiple pathways. The current paper is a scoping review of translational, observational, and interventional evidence on the potential role of selenium and its compounds in the ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(172 reference statements)
0
1
0
Order By: Relevance
“…In a recent study examining the relationship between reduced selenium levels and anxiety, the findings revealed a heightened risk of generalized anxiety disorder linked to lower serum concentrations of selenium [ 166 ]. Corresponding research has identified a connection between deficient selenium levels and minor and major depressive disorder [ 167 , 168 ]. Recent findings also suggest that selenium might have a significant role in maintaining normal neural function after experiencing stress, which is pertinent to developing and continuing anxiety disorders [ 169 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study examining the relationship between reduced selenium levels and anxiety, the findings revealed a heightened risk of generalized anxiety disorder linked to lower serum concentrations of selenium [ 166 ]. Corresponding research has identified a connection between deficient selenium levels and minor and major depressive disorder [ 167 , 168 ]. Recent findings also suggest that selenium might have a significant role in maintaining normal neural function after experiencing stress, which is pertinent to developing and continuing anxiety disorders [ 169 ].…”
Section: Resultsmentioning
confidence: 99%